Economic projection of representative production units of caprine cattle in the Comarca Lagunera region, Mexico - Orona Castillo, Ignacio; Sangerman-Jarquín Dora Ma.; Antonio-González Jacob; Salazar Sosa, Enrique; García Hernández José Luis; Navarro-Bravo Agustín; de Rindermann, Rita Schwentesius Schwentesius (Revista Mexicana de Ciencias Agrícolas, 2018)
In México, caprine cattle breeding is important due to the families living in rural areas who depend on the activity; according to estimations made by the National Institute for Statistics and Geography, there are about 250 thousand animals in México. Nevertheless, traditionally and so as to show support for this activity, the Mexican government, represented by the Ministry of Agriculture, Stockbreeding, Fishing and Food, considers that all the producers who breed goats have access to the same technology, and that all of them produce the same thing. In reality, producers have differences according to the region, entity and even within the same township, and so the type of support they receive must be according to their needs and characteristics. The objective of this paper is to present the economic and financial feasibility projection for a Representative Production Unit (URP, in Spanish), which would produce milk and kid, under an extensive production system for the period that goes from 2008-2018, in the municipality of Lerdo, Durango, located in the region known as Comarca Lagunera, taking as baseline year the economic behavior shown by the URPs in 2008, and deriving from it the identification of the technologic components which need support in order to increase the profitability of this kind of productive system. The data required to undertake this study and establish the milk and kid producing URP, came from panel s of producers presented at the common land of La Loma, state of Durango. The economic and simulation analysis was realized within the agro-economic simulation model MexSim, which results show a positive behavior in the future for the producers focused in this activity, who own a herd of 100 breeding stock, and produce milk and kid.